1996
DOI: 10.1073/pnas.93.8.3193
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modulation by transforming growth factor beta in human tuberculosis: suppression of antigen-driven blastogenesis and interferon gamma production.

Abstract: In tuberculosis, Mycobacterium tuberculosis (MTB)-stimulated T-cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
144
2
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(152 citation statements)
references
References 46 publications
(17 reference statements)
5
144
2
1
Order By: Relevance
“…MTB and its major protein and polysaccharide constituents are potent inducers of production of cytokines in mononuclear phagocytes, some of which, such as TGF-␤, are immunosuppressive and macrophage deactivating (8)(9)(10)(11)(26)(27)(28). The recruitment of MN to sites of active MTB infection and activation of MN to production of cytokines, in particular TGF-␤, may be important in the immunopathogenesis of TB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MTB and its major protein and polysaccharide constituents are potent inducers of production of cytokines in mononuclear phagocytes, some of which, such as TGF-␤, are immunosuppressive and macrophage deactivating (8)(9)(10)(11)(26)(27)(28). The recruitment of MN to sites of active MTB infection and activation of MN to production of cytokines, in particular TGF-␤, may be important in the immunopathogenesis of TB.…”
Section: Discussionmentioning
confidence: 99%
“…Excess TGF-␤ underlies the depressed in vitro T cell responses to MTB antigens in patients with TB, as coculture of peripheral blood mononuclear cells (PBMCs) from TB patients with neutralizing antibody to TGF-␤ normalizes T cell blastogenesis and enhances production of interferon ␥ (IFN-␥) (10). IFN-␥ appears to play a central role in limiting MTB infection, as recently shown in the murine models of TB (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neither cell proliferation nor antibody production completely reflect the expression or absence of protective immunity against tuberculosis, which may be mediated by the production of IFN-g [12,13]. Therefore, five BCG-SH and five patients with pleural or pulmonary disease were examined for the ability of the recombinant antigen to elicit IFN-g.…”
Section: Interferon-g and Il-10 Production In Response To The 16 Kda mentioning
confidence: 99%
“…We and others have shown that M. tuberculosis-induced IFN-␥ production and mRNA expression are reduced in tuberculosis patients, compared with healthy tuberculin reactors (2,3,19,20). Transcription of the IFN-␥ gene depends on binding of specific nuclear proteins to the IFN-␥ promoter (10 -14).…”
Section: Complexes Binding To the Proximal Ifn-␥ Promoter Region In Tmentioning
confidence: 99%